RELEVANSI AL-QUR’AN DENGAN FALSAFAH MADURA BHUPPA’ BHABHU’ GHURU RATO (Kajian Analisis: QS. Al-Nisa’: 59, QS. Al-Isra’: 23-24 dan al-Kahfi: 66-82 Perspektif Ibnu Kathir dalam tafsir al-Qur’an al-‘Adzim.) - As’ari As’ari (Journal of Innovative and Creativity, 2026)
Marriage is something scared to society in Pamekasan, special for pious people. They don’t easily choose couple for their children. There are many aspects that is done by them to choose the best couple for their children, so that many pious people choose a couple from the same circel and it becomes a tradition, so that very diffucult to dissapear it. This reasearch is qualitative research that consist of field researc, this research has purpose to discribe and answer many problems related to marriage tradition in pious people circle, specially in Pamekasan, that it refers to the kafaah nasab and al-Qur’an perspective about kafaan nasab in wedding. In this research data collection use primer and sekunder data and then all of the data analyzed by describtive methode (analyzing-explanation). From the data of research that is got from informant an references, so the result of this research states that, the first is marriage tradition in pious people area, specially in Pamekasan is taken by some aspects: 1. Kafaah in dominant family. 2. Kafaah in social status. 3. Kafaah in religion. The second is based on al-Qur’an Persepective about kafaah nasab in marriage from the verse of al-Qur’an, there is no clear explanation. It means that there is no dissent from all of group because all of humanity have the same part in Allah perspective, except the level of piety. But based on the reality kafaah nasab in pious people area is still existence until now